Comparison of various machine learning regression models based on Human age prediction - Dr.Manaf K Hussein (Wasit Journal of Engineering Sciences)
The development of machine learning strategies has made it possible to diagnose some disease automatically based on data obtained from medical imaging. Brain age is one of the factors that can be used as an indicator of cognitive well-being. Recent advancements in machine learning have made it possible for computers to anticipate classification and prediction outcomes more accurately than humans.